A coupled Integral Transform Method - Finite Element Method approach to model the Soil Structure Interaction of finite (3D) and length invariant (2.5D) systems. (15th September 2020) - Freisinger, J.; Hackenberg, M.; Müller, G.
Abstract: The prediction of vibrations in an unbounded medium and their interaction with structures on the ground surface or within the soil requires adequate approaches. Therefore the numerical methods addressing the dynamic Soil Structure Interaction (SSI) have to account for both, the infinite extent of the soil by satisfying the radiation condition for the wave propagation towards infinity and the detailed modeling of complex geometries and material properties of the considered structures. In this contribution an efficient domain decomposition method to model the three dimensional SSI is presented using a coupled Integral Transform Method (ITM) - Finite Element Method (FEM) approach. Based on the Lamé differential equation, fundamental solutions for systems with one boundary surface, as a halfspace or a fullspace with either spherical or cylindrical cavity, can be derived using the ITM. These are superposed to determine solutions of systems with two boundary surfaces: the halfspace with spherical or cylindrical cavity. The FEM is used to model the structure possibly within a limited volume of surrounding soil, which then is coupled to the ITM substructure on the cylindrical or spherical interaction surface. The practical applicability and high accuracy of the method is demonstrated by comparison with the analytical solution of fundamental systems and the investigation of typical SSI problems such as a mitigation measure in the transmission path and a rigid surface footing on a homogeneous soil.